Relapse of severe acute malnutrition among children discharged from outpatient therapeutic program in western Ethiopia - Endalkachew Befekadu Teshale; Yakob Desalegn Nigatu; Tefera Darge Delbiso (BMC, 2023)
Abstract Background Children with severe acute malnutrition (SAM) without complication are treated in the outpatient therapeutic program (OTP) and the program has been reported to be effective. However, relapse post-discharge from the program is poorly defined, and scarcely evaluated across programs and research. The objective of this study is to assess the prevalence of SAM among children post-discharge from the OTP and to identify factors associated with SAM relapse in Gambella Region, Western Ethiopia. Methods We conducted a facility-based cross-sectional study among 208 children aged 6-59 months who have been discharged from the OTP as cured. Baseline data were collected from caregivers using structured questionnaire. Child anthropometry and oedema was measured. The association between SAM relapse and the risk factors were assessed using bivariate and multivariable logistic regression models. Results The prevalence of SAM relapse was 10.1% (95% CI: 5.8-14.0%). The odds of SAM relapse was significantly higher in children with mothers who had no exposure to education and promotion about infant and young child feeding (IYCF) practices (OR = 5.7; 95% CI: 1.3-12.6), children who were not fully immunized for their age (OR = 8.0; 95% CI: 3.8-23.4), and children with mid-upper arm circumference (MUAC) at discharge of < 12.5 cm (OR = 4.4; 95% CI: 2.1-12.8) than their counterparts. Conclusions To reduce SAM relapse, the OTP programs should avoid premature discharge and consider provision of supplementary food for children with low MUAC at discharge. Further, the OTP discharge criteria should consider both the anthropometric indicators - weight-for-height/length z-score (WHZ) and MUAC - and the absence of bilateral pitting oedema irrespective of the anthropometric indicator that is used during admission. Promotion of nutrition education and improving child immunization services and coverage would help reduce SAM relapse.